Association between safety leading indicators and safety climate levels. (September 2017) - Givehchi, Saeed; Hemmativaghef, Ehsan; Hoveidi, Hassan
Abstract: Objectives: The aim of this study was to evaluate the association of leading indicators for occupational health and safety, particularly safety inspections and non-compliances, with safety climate levels. Methods: Nordic Occupational Safety Climate Assessment Questionnaire was employed to evaluate safety climate in cross-sectional design. The geographically diverse population of the inspection body made it possible to conduct the survey across 10 provinces in Iran. 89 completed questionnaires were obtained with a response rate of 47%. Except for management safety justice, the internal consistency of other six dimensions was found to be acceptable (α ≥ 0.7). Results: Mean scores of dimensions ranged from 3.50 in trust in the efficacy of safety systems (SD = 0.38) to 2.98 in workers' safety priority and risk non-acceptance (SD = 0.47). Tukey HSD tests indicated a statistically significant difference of mean scores among groups undergoing different number of safety inspections and those receiving different number of non-compliances (p < 0.05), with no significant differences based on safety training man-hours and sessions (p > 0.05). Spearman's rank-order correlation showed no relationship between work experience and number of non-compliances (correlation coefficient = − 0.04, p > 0.05) and between safety training man-hours and number of non-compliances (correlation coefficient = − 0.15, p > 0.05). Conclusions: Our results indicate that safety climate levels are influenced by number of safety inspections and the resultant non-compliances. Practical applications: Findings suggest that safety non-compliances detected as a result of conducting safety inspections could be used to monitor the safety climate state. Establishing plans to conduct scheduled safety inspections and recording findings in the form of safety non-compliance and monitoring their trend could be used to monitor levels of safety climate. Highlights: Employing number of safety inspections and non-compliances as potential confounders on safety climate levels. A geographically diverse study population spread across 10 cities and ports. Comparison of present study data with the overall data from all studies carried out using the same survey questionnaire. The study population comprised of inspectors of traded goods, for which very few studies had been conducted.